THU0096 Targeting Lymphatic Dysfunction in Rheumatoid Arthritis by High-Density Lipoprotein. (23rd January 2014) - Bisoendial, R.; Roediger, B.; Jain, R.; Cavanagh, L.; Tak, P.-P.; Rye, K.-A.; Weninger, W.
Abstract : Background: Rheumatoid arthritis (RA) is increasingly recognized to raise cardiovascular (CV) risk by two-fold. Our peliminary in vitro findings suggest that high-density lipoprotein (HDL) and its main apolipoprotein (apo)A-I may correct lymphatic dysfunction, a hallmark of chronic inflammation. Objectives: The impact of an i.v. injection of human apoA-I (40 mg/kg) or reconstituted (r)HDL - consisting of phosphatidylcholine with apoA-I - was evaluated on key lymphatic properties and resolution of inflammation in an acute mouse ear skin inflammation model. Methods: Inflammation was induced by intra-dermal injection of 2.5 ug of lipopolysaccharide (LPS; O55:B5), in animals that had received apoA-I, rHDL or PBS 24 hrs earlier. Two days after LPS-injection, i.e. the peak of inflammation, ear swelling and erythema were scored. The auricular draining lymph node (DLN) was harvested for flow cytometry to assess changes in inflammatory cell migration. Alexa594-LPS was used to study LPS clearance from ear to DLN using an in vivo imaging system (IVIS). Lymph flow from ear skin to DLN was monitored 15 min after injecting 1.5 ul of TexasRed-Dextran (TXR-DX) at the inflammatory site using a stereomicroscope and IVIS. Results: Erythema and swelling upon LPS were not significantly affected by pre-treatment with rHDL or apoA-I (24.8% and 38.4% increase respectively, as compared to PBS 36.7%). After 48 hrs, the influx of inflammatory cells in the DLN was significantly reduced upon pretreatment with rHDL and apoA-I (absolute cell numbers per DLN: PBS: 1x10 7 ±2x10 6 ; rHDL: 2x10 6 ±4x10 5 and apoA-I: 5x10 6 ±1x10 6 ). Particularly the numbers of neutrophils (632.5±388.9 and 2610±1395 for rHDL and apoA-I, as compared to 16788±5340 for PBS) and CD11c + MHC-II high migratory dendritic cells (DC; 4873±1820 and 20680±7005 for rHDL and apoA-I, as compared to 41170±9495 for PBS) were diminished (all p<0.05). Compositional changes of leukocytes in the peripheral blood and spleen were less remarkable. Intravital monitoring of ALEXA594-LPS using IVIS showed similar LPS disappearance from the ears after 24 hrs (decrease 66.2% and 51.8% for rHDL and apoA-I respectively, as compared to PBS 73%). In line, fluorescence intensity of ALEXA594-LPS in the DLN after 48 hrs seemed unaffected by pretreatment with rHDL and apoA-I. Lymphangiography using TXR-DX revealed that LPS resulted in dysmorphic patterning of lymphatic vessels and hyperpermeability, pointing to functional impairment. Pretreatment with apoA-I resulted in less pronounced hyperpermeability and higher fluorescence recovery of TXR-DX in the DLN. Conclusions: Lymphatic properties comprising lymph flow and inflammatory cell migration that includes neutrophils and migratory DCs, is suggested to improve upon prior systemic administration of HDL and apoA-I in this LPS-induced ear skin inflammation model. Awaiting further results that may clarify the involved mechanisms and outcomes in chronic inflammation models these data support therapeutic benefits of HDL-based approaches in RA by targeting lymphatic dysfunction and thereby reducing CV risk. Disclosure of Interest: None Declared